Compensation for Motor Vehicle Injuries in New Zealand - Miller, John (Les Cahiers de droit, 1998)
Compensation for Motor Vehicle injuries in New Zealand is included as part of the overall no fault accident compensation scheme in the Accident Rehabilitation and Compensation Insurance Act 1992. This Act replaced the Accident Compensation Act 1982 and abolished lump sum compensation for injuries and excluded mental trauma injury claims which were available under the previous Act. This led to considerable public dissatisfaction with the 1992 Act and brought lawyers back into the compensation process with damages claims for mental trauma injuries. The renewed interest of lawyers in litigation also led to an increase in exemplary/punitive damages claims. Despite this return to litigation the motor vehicle part of the no fault scheme presents few problems. It is well funded and is well accepted apart from the recurrent question of compensating drunken drivers for their injuries.